Shadow throne eaudiobook - Nielsen, Jennifer A. (Ascendance, 2017)
Jennifer A. Nielsen takes readers on an extraordinary journey with the False Prince in this third installment of the New York Times and USA Today bestselling Ascendance Series. War has come to Carthya. It knocks at every door and window in the land. And when Jaron learns that King Vargan of Avenia has kidnapped Imogen in a plot to bring Carthya to its knees, Jaron knows it is up to him to embark on a daring rescue mission. But everything that can go wrong does.His friends are flung far and wide across Carthya and its neighboring lands. In a last-ditch effort to stave off what looks to be a devastating loss for the kingdom, Jaron undertakes what may be his last journey to save everything and everyone he loves. But even with his lightning-quick wit, Jaron cannot forestall the terrible danger that descends on him and his country. Along the way, will he lose what matters most? And in the end, who will sit on Carthya's throne? And don't miss the highly anticipated fourth book in the series, The Captive Kingdom , coming October 2020!